Bactericidal Effect of Combination of Atmospheric Pressure Plasma and Nisin on Meat Products Inoculated with Escherichia coli O157: H7 - Hag Ju Lee; Yeseul Heo; Hye-Jin Kim; Ki Ho Baek; Dong-Gyun Yim; Sethukali, A.; Dongbin Park; Cheorun Jo (The Korean Society for Food Science of Animal Resources, 2023)
This study was conducted to investigate the bactericidal effect of nisin (Nisin) only, atmospheric pressure plasma (APP) only, and a combination of APP and nisin (APP+Nisin) on beef jerky and sliced ham inoculated with Escherichia coli O157:H7, gram- negative bacteria. The bactericidal effect against E. coli O157:H7 and Listeria monocytogenes was confirmed using a nisin solution at a concentration of 0–100 ppm, and APP+Nisin was tested on beef jerky and sliced ham using 100 ppm nisin. Beef jerky and sliced ham were treated with APP for 5 min and 9 min, respectively. In the bacterial solution, 100 ppm nisin out of 0–100 ppm nisin exhibited the highest bactericidal activity against L. monocytogenes (gram-positive bacteria; p<0.05); however, it did not exhibit bactericidal effects against E. coli O157:H7 (gram-negative bacteria). The APP+Nisin exhibited a 100% reduction rate in both E. coli O157:H7 and L. monocytogenes compared to the control group, and was more effective than the Nisin. The APP+Nisin decreased the number of colonies formed by 0.80 and 1.96 Log CFU/g for beef jerky and sliced ham, respectively, compared to the control, and exhibited a higher bactericidal effect compared to the Nisin (p<0.05). These results demonstrate the synergistic bactericidal effect of APP and nisin, providing a possible method to improve the limitations of nisin against gram-negative bacteria. In addition, this technology has the potential to be applied to various meats and meat products to control surface microorganisms.
Keywords: Atmospheric pressure plasma; Nisin; Gram-negative bacteria; Meat products; Bactericidal effect